Evaluating managers diversification of real estate portfolios: Evidence from Nigeria - Olaleye, Abel; Aluko, Bioye Tajudeen (International Journal of Strategic Property Management, 2010)
While there is evidence on the effectiveness of diversifying real estate portfolio geographically, or by property type, there is lack of empirical evidence to justify whether diversification of managers is worth pursuing. This study produces evidence on the effectiveness of diversifying by managers and property types. The study collected data on capital and annual rental values from three (3) main Property Investment and Development Companies in Lagos Metropolis, Nigeria. From the data so collected, annual total returns (IRR), on residential properties, for a period of between 1997 and 2001 on the managers’ portfolio were calculated. Under the assumptions that investments are held long and that constant correlation model or excess return to standard deviation represents the covariance structure of assets’ returns, the study's analyses suggest that diversification of managers and property types produce improved performance. It also opens the possibility that an efficient portfolio developed by using constant correlation analysis may not be more efficient than a naively diversified portfolio as some of the naive diversification strategies are found to be effectively efficient.First published online: 18 Oct 2010